RISK QUOTIENT OF ZINC (Zn) AND CHROMIUM (Cr) LEVEL IN DUG WELL WATER IN THE COMMUNITY LIVING AROUND LANDFILL SITE - Maksuk, Maksuk; Dewi Ulfa Oktarini; Tria Effrilia Harahap; Maliha Amin; Maya Sopianti; Khairil Anwar; Kamsul, Kamsul (Indonesia Epidemiological Journal, 2023)
ABSTRACT Background: Zinc and chromium are heavy metals that can contaminate community-dug well water that is used by people around landfills, and can cause public health problems. This study aimed to analyze the risk level of zinc (Zn) and chromium (Cr) content in the dug well water of the community around Sukawinatan landfill site. Methods: This research was an observational study using a cross-sectional design with an environmental health risk analysis approach, It was conducted in February–May 2021. The sample was water from the dug wells of the community that lives around the Sukawinatan landfill. The examination of zinc and chromium level in dug well water was used the Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES) method. Results: Zinc and chromium level in community dug well water was found to range from 0.03 mg/l to 0.09 mg/l for zinc concentration and from 0.0030 mg/l to 0.04 mg/l for chromium concentration, respectively. The results of calculating the potential dose (intake) for the two metals are still below the dose reference value, and for calculating the level of risk, the result is less than 1, which can be interpreted as not being risky.  Conclusion: Zinc and chromium level in the community's dug-well water around the landfill site was still below the quality standard. The potential dose (intake) and Risk Quotient were safe for the next few years.